2014
DOI: 10.1038/clpt.2014.129
|View full text |Cite
|
Sign up to set email alerts
|

Functional Gene Variants of CYP3A4

Abstract: Cytochrome P450 3A4 (CYP3A4) is involved in the metabolism of more drugs in clinical use than any other foreign compound–metabolizing enzyme in humans. Recently, increasing evidence has been found showing that variants in the CYP3A4 gene have functional significance and—in rare cases—lead to loss of activity, implying tremendous consequences for patients. This review article highlights the functional consequences of all CYP3A4 variants recognized by the Human Cytochrome P450 (CYP) Allele Nomenclature Database.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(166 citation statements)
references
References 73 publications
4
137
0
9
Order By: Relevance
“…Genotypic variation in CYP2C9 and CYP3A4 alleles can lead to alterations in the activity of these enzymes (Kirchheiner and Brockmoller, 2005;Werk and Cascorbi, 2014), which has the potential to alter the balance between bioactivation and detoxification, and thus alter the relative abundance of reactive and stable TMP metabolites. Further studies assessing in vivo TMP bioactivation are needed to better understand the extent and variability of TMP bioactivation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Genotypic variation in CYP2C9 and CYP3A4 alleles can lead to alterations in the activity of these enzymes (Kirchheiner and Brockmoller, 2005;Werk and Cascorbi, 2014), which has the potential to alter the balance between bioactivation and detoxification, and thus alter the relative abundance of reactive and stable TMP metabolites. Further studies assessing in vivo TMP bioactivation are needed to better understand the extent and variability of TMP bioactivation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…[40] This variant is a c.802C>T transition and results in a premature stop codon at position 268 in exon 9 (R268*). [40] The resulting truncated CYP3A4 protein is nonfunctional.…”
Section: Cyp3a4mentioning
confidence: 99%
“…[40] This variant is a c.802C>T transition and results in a premature stop codon at position 268 in exon 9 (R268*). [40] The resulting truncated CYP3A4 protein is nonfunctional. Werk et al [41] first identified this mutation when they observed an unusually low Tac dose requirement in a kidney transplant recipient.…”
Section: Cyp3a4mentioning
confidence: 99%
“…8 Functional variants in the CYP3A4 gene that may have functional effect have been characterized, but they are rare in Caucasian population. 17 One of the most common functional variants, CYP3A4*22 allele that leads to decreased enzyme activity has a frequency of 5-7% in Caucasian populations. 18 Therefor we would need a much larger sample to investigate the potential role of this polymorphism in 21OHD genotype -phenotype inconsistency.…”
Section: Resultsmentioning
confidence: 99%